2018
DOI: 10.1002/jsfa.8888
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and intestinal immunomodulating activities of water‐soluble pectic polysaccharides from Chenpi with different storage periods

Abstract: The present study demonstrates the differences in the pectic polysaccharides from Chenpi with different storage periods and also confirms that the pectic polysaccharides extracted from Chenpi stored over the long-term had more significant intestinal activities compared to that obtained from the fresh Chenpi. This phenomenon might partly explain why the Chenpi stored over the long-term has better healthcare effects. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
(32 reference statements)
4
12
0
Order By: Relevance
“…Compared with BP, LPs had more complex monosaccharide compositions. This is similar to the finding of a previous study in that with the extension of the storage period of Chenpi, the number of types of monosaccharides increased in the polysaccharide [ 34 ]. The content of Man and Rha in BP was much higher than that in the LPs, whereas the monosaccharide compositions present in the LPs were typical for pectic polysaccharides, which mainly consisted of Rha, Gal, and Gal-A [ 35 ].…”
Section: Resultssupporting
confidence: 91%
“…Compared with BP, LPs had more complex monosaccharide compositions. This is similar to the finding of a previous study in that with the extension of the storage period of Chenpi, the number of types of monosaccharides increased in the polysaccharide [ 34 ]. The content of Man and Rha in BP was much higher than that in the LPs, whereas the monosaccharide compositions present in the LPs were typical for pectic polysaccharides, which mainly consisted of Rha, Gal, and Gal-A [ 35 ].…”
Section: Resultssupporting
confidence: 91%
“…CRP has long been used in traditional medicine for treating digestive tract diseases and anti-inflammatory diseases; it is also used as a seasoning in cooking and as a dietary supplement (13). Studies have shown that its extracts and active ingredients may improve glycolipid metabolism disorder by regulating the gut microbiome (14)(15)(16)(17). Therefore, CRP extract was selected as an intervention drug in this study and its possible mechanism in glycolipid metabolism disorder was explored in juvenile C57BL/6 mice referred to existing researches (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The changes of odor efficacy may be attributed to the dynamic variation of phytochemical and volatile compounds. Tian et al (2018) demonstrated that the water-soluble pectic polysaccharides obtained from CRP stored for a long period contained more conjugated phenolic acids and stronger intestinal activities compared with that obtained from fresh CRP. Luo et al (2019) have found different phytochemical metabolites in CRP with different storage years.…”
Section: Introductionmentioning
confidence: 98%